Exploring biomedical ontologies, personalized pagerank and semantic similarity in the entity linking task - Ruas, Pedro Simões (2019)
Tese de mestrado, Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2019